THU0569 Treatments of uveitis in a referral multidisciplinary unit in northern spain. (15th June 2017) - Fanlo, P; Heras, H; Terry, O; Espinosa, G; Adan, A
Abstract : Background: Intraocular inflammation is one of the leading causes of visual impairment and blindness. Early and appropiate treatment is mandatory for avoiding complications. Objectives: To describe the treatments prescribed in a cohort of patients with uveitis in a referral multidisciplinary unit from northern Spain. Methods: Retrospective analysis of clinical records of patients evaluated in the Uveitis Multidisciplinary Unit of the Complejo Hospitalario of Navarra since January 2010 until March 2015. We analyzed the demographic characteristics and treatments received in the following 3 months after first visit. Results: We identified 500 patients, 50% women with a mean age of 47.9 +/- 16.4 years. The most frequent type of uveitis was anterior uveitis (65, 4%), followed by posterior uveitis (17, 6%), panuveitis (15, 2%), and intermediate uveitis (1, 8%). Considering the etiology, 31.2% were unclassifiable, followed by non-infectious systemic disease in 29.2%.During the 3-month follow-up, 904 treatments were prescribed. The most frequent treatment was ocular topical (39%), followed by immunosuppressive treatment (27%), antimicrobial (14%), other treatments (10%) and less biological (3%), surgical (3%) and finally periocular (2%) and intravitreal (2%) treatment.Topical ocular treatment: 350 patients received topical ocular treatment, which accounts for 70% of patients. Among topical ocular treatments, 15% of the samples were treated with topical steroids, 54% were topical steroids associated with another topical treatment, 2% were topical antiglaucomatous, 2% received other topical treatments and 27% of the sample did not receive topical treatment.Immunosuppressive treatment: 249 immunosuppressive treatments were prescribed. 50% of the patients received immunosuppressive treatment. Among the immunosuppressive treatments, 25% of the patients received oral steroids, 6% salazopyrine, 4% methotrexate, 5% azathioprine, 2% mycophenolate mofetil, 5% oral steroids associated with another immunosuppressant, 15% salazopyrine associated with another immunosuppressant, 1% other immunosuppressive treatment and 49% of patients did not receive any immunosuppressive treatment.Biological Treatments: 25 patients in the cohort received biological treatment, this represents 5% of patients. The biological treatment types were distributed as follows: 3% of the patients received adalimumab treatment, 1% received infliximab, 1% received other biological treatments, and 95% of the patients did not receive biological treatments.The number of treatments received per patient was analyzed and 50 patients (10%) received no treatment, 152 patients (30%) received 1 treatment, 189 patients (38%) received 2 treatments, 75 patients (15%) Had received 3 treatments, 23 patients (5%) had received 4 treatments, 9 patients (2%) had received 5 treatments and lastly 2 patients had received 6 treatments. Conclusions: The majority of patients received the combination of two treatments. Topical steroids and oral steroids were the most frequent treatments used. Disclosure of Interest: None declared